Secured Private Cloud Storage - Adlan, Muhammad Faisal (Journal of Computing Technologies and Creative Content, 2019)
Nowadays people keep their data in the internet storage also known as cloud storage. The capability of cloud storage is keep the data in a larger amount of size. It can be access anywhere, anytime and it is very fast to view the file that has been kept. Unfortunately, like any other type of cloud storage, majority of these systems are vulnerable to malicious attacks and have privacy issues with the safety of the data and stolen data from unknown source. The need to identifying security services to make sure the cloud storage is secure and safe from the users to use. This research proposes latest development of security aspect to make users had the system with better integrity, confidentiality and privacy. Research being conducted to investigate current security features of popular cloud d storage that available in current technology. A list of requirements for good security is generated and based on those requirements an architecture is designed.